Minat Penggunaan Aplikasi Flip ditinjau dari Kemudahaan, Manfaat, Fitur layanan, dan Kepercayaan pada Reseller Beteng Trade Center - Saputri, Gita Andini; Maryam, Siti; Marwati, Fithri Setya (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to analyze the effect of Perceived Ease of Use, Perceived Usefulness , service features and trust on interest in using the Flip Application. The population in this study were 105 Beteng Trade Center resellers who had used Flip. The results show that Perceived Ease of Use, Perceived Usefulness, have no effect on interest in using the Flip Application, while service features and trust have a positive and significant influence on interest in using the Flip Application. Keywords: Perceived Ease of Use, Perceived Usefulness, service features, trust, interest in use.